Cultural Factors in a Mobile Phone Adoption and Usage Model: A Case of UUM Postgraduate Students - Azela Aqilah, Rasul (2011)
Mobile phone is one of the communication devices that can meet requirement where it consists of an integrated system of technology and socially derived components. The technology that provided in mobile phone keep changing by the features and there a lot in the market today. Hence, the upgrading technology will influence user behavior. For that, the objective of this research is to identify on the factors that influence mobile phone adoption and usage and evaluate on significant between human behavior pattern and technology in mobile phone. To be success in this research, quantitative and qualitative approach has been used to explore, observation and cultural analysis. Meanwhile, the results also indicated that variable need for achievement contributes high influence in social factors that influence mobile phone adoption and usage, where it is the components of human nature and culture